Hubungan Pengetahuan Ibu dengan Pola Menu Sarapan dan Kebiasaan Sarapan pada Anak Sekolah Dasar - Faradina Aghadiati (Poltekkes Kemenkes Maluku, 2019)
The problem which is found in elementary school students is leaving their breakfast. There are several researches shown the high frequency for leaving meals (especially breakfast) will cause disruption growth and bad academic achievement. There are many factors which make elementary school students leave their breakfast. Breakfast habit on elementary school students needs parents guiding for making the habit and providing the breakfast menus. It needs parents guiding especially mother. The research goal is to know the relationship of mother’s knowledge with breakfast menus pattern and breakfast habits on elementary school students. The research belongs to the analytical observation research that using cross sectional program. The research subjects are 90 elementary school students in 5th grades and their mother who are taken randomly. The data such as respondent characteristics, knowledge level are found out from the questionnaires. The breakfast menus pattern is found out from the food record form. The breakfast habits on child are found out from the food interview form. The data analysis uses Chi-square. There is significant between mother’s knowledge with the breakfast menus pattern (p < 0,05). There is no significant between breakfast menus pattern with the breakfast habits (p > 0,05). There is significant between mother’s knowledge with the breakfast habits (p < 0,05). Mother’s knowledge is related with the breakfast menus pattern and breakfast habits while breakfast menus pattern is not related with breakfast habits. Keywords: Breakfast, breakfast habits, breakfast menus pattern, mother’s knowledge